Financial Management and Business Development at the Buana Collection Convection UMKM, Kotabaru District, Karawang - Ludi Jamaludin; Maulana Yusuf Assidiq; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of the Industrial Visit activity for the Convection Micro, Small and Medium Enterprises (MSMEs) is to find out the financial management and business development applied to the Buana Collection Convection SMEs. The industrial visit method is carried out by interviews and direct discussions with MSME actors. The activity phase that will be carried out is in the form of observational studies and information gathering. Data collection is a systematic procedure and is a standard for obtaining the necessary data. Data collection was carried out based on direct observation to the field (field research) visiting data sources by observing and interviewing direct objects. The results obtained during this industrial visit were in the form of obtaining information about financial management that is commonly used and providing information related to how financial management and business development can be used to help increase sales of clothing products by MSME actors. The results of the study show how financial management and business development are implemented by MSMEs, namely financial management behavior that is not recorded, it can be seen that there is no special notebook for business finances, while developing business opportunities the strengths and opportunities of MSMEs are quite large, this can be seen from the analysis of external factors and internal.